Community Participation as a Moderating: Effect of Village Officials’ Competence on Fund Accountability - Andri Widianto; Nurul Mahmudah; Destiana Artanti (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study aims to analyze the effect of village officials’ competence on the accountability of Village Fund management and examine the moderating role of community participation in strengthening this relationship. Research Methodology: A quantitative research design was employed using survey data collected from 97 village officials in Tegal Regency through purposive sampling method. Data were obtained via offline questionnaires and analyzed using SmartPLS. Results: The findings indicate that village officials’ competence significantly and positively affects Village Fund management accountability. Furthermore, community participation significantly moderates and strengthens the relationship between competence and accountability, suggesting that higher public involvement enhances the effectiveness of good governance in achieving transparency and responsible financial management. Conclusions: Accountability in Village Fund management is influenced by the competence of village officials and active community participation as a reinforcing factor. The synergy between professional capacity and participatory oversight is essential for realizing transparent and accountable village governance. Limitations: The small sample size is insufficient for generalization, so further research should be conducted with a larger sample size, not limited to Tegal Regency. Furthermore, the moderating variable is only one, so future research should consider internal control systems, organizational culture, or information technology maturity. Contributions: This study provides substantial theoretical, empirical, and practical contributions in the field of village fund governance. Theoretically, the authors successfully integrate Stewardship Theory with Good Governance perspectives within a moderation framework.